Examining the effectiveness of a family‐focused training to prevent youth suicide. Issue 1 (17th May 2022) - Schuck, Allison; Gryglewicz, Kim; Bender, Ansley; Nam, Eunji; McNeil, Marissa; Cosare, Michael; Rosler, Melanie; Karver, Marc
Abstract: Objective: The present study investigates the effectiveness of a novel, consumer‐informed, family training for youth suicide prevention. Background: Research suggests family members play a key role in reducing suicide risk for their children. However, family members often do not possess the necessary knowledge, confidence, and skills needed to intervene with a suicidal youth. Method: Family members ( N  = 582) participated in the It's Time to Talk About It: Family Training for Youth Suicide Prevention (ITT‐FT) and completed pretest and posttest measures. Additionally, 158 family members completed a 6‐month follow‐up evaluation. Results: Results indicated significant improvements in knowledge, effective attitudes, perceived behavioral control, social norms, and intentions immediately after the training. Knowledge and perceived behavioral control were sustained at follow‐up. Participants identifying as Hispanic/Latinx exhibited greater decreases in stigma related to help‐seeking. Those who had a family history of mental health treatment experienced a greater increase in social norms related to other families seeking help. Conclusion: Findings underline the importance of implementing a family‐focused program aimed at improving training outcomes such as knowledge, confidence, and intentions—key constructs associated with behavior change. Implications: Improvement in several domains following the training highlight the critical role family members can play in reducing youth suicide risk.